3x-6+13x-6=180

Simple and best practice solution for 3x-6+13x-6=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6+13x-6=180 equation:


Simplifying
3x + -6 + 13x + -6 = 180

Reorder the terms:
-6 + -6 + 3x + 13x = 180

Combine like terms: -6 + -6 = -12
-12 + 3x + 13x = 180

Combine like terms: 3x + 13x = 16x
-12 + 16x = 180

Solving
-12 + 16x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 16x = 180 + 12

Combine like terms: -12 + 12 = 0
0 + 16x = 180 + 12
16x = 180 + 12

Combine like terms: 180 + 12 = 192
16x = 192

Divide each side by '16'.
x = 12

Simplifying
x = 12

See similar equations:

| 4b+7=25 | | 4x^2+3x=9 | | 4[6-(-5x-6)]=40x+72 | | 3(w+7)=-3(7w-1)+9w | | 7c*6e= | | 8x+10y=48 | | 5a/4-2a/5=17/2 | | 2(x-3)-3=-4(-5x+3)-3x | | 3x+7-5(x-1)=5x+4 | | 8r+10y=48 | | 8x-9-6x+14=11x-9-10+13 | | -7.24=x/4+3 | | a*2/(4+6)=10 | | 15x^2+19m+6=0 | | -5x+15.8=3.3 | | 3-4(5-7)=z | | Z+6/8=Z-5/7 | | -3(3v-7)+7v=6+3(2v-1) | | -1.1+u/2=-13.9 | | 6=-19+t | | 7(x+4)=-3(x+2)+4 | | 5+2u=19 | | .3x+2=2.6 | | 25=-14+y | | -3+4(-2+7)= | | -24=w/4-4 | | (3)/(x^2-2x)-(2)/(x)=(8)/(x-2) | | 8+6v=6v-6+7v | | 3y-2+3(2y+1)=-3(y+3) | | 58=-x+171 | | y-(-9)=(-14/3)(x-(-9)) | | x/37+25=50 |

Equations solver categories